2018
DOI: 10.1038/s41598-018-34045-y
|View full text |Cite
|
Sign up to set email alerts
|

More evening preference is positively associated with systemic inflammation in prediabetes and type 2 diabetes patients

Abstract: Currently it is not known whether morningness-eveningness preference in non-night shift working population is associated with systemic inflammation. This study investigated the relationship between morningness-eveningness and systemic inflammation, as measured by high-sensitivity C-reactive protein (hs-CRP) in 163 non-night shift working patients with abnormal glucose tolerance (86 type 2 diabetes and 77 prediabetes). Morningness-eveningness was assessed by Composite Scale of Morningness, and participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…This link between chronotype and misalignment was also suggested in a study of 163 prediabetic or type 2 diabetic individuals’ eating and sleeping patterns. This study found that, after adjusting for age, sex, BMI, and statin use, a late chronotype was associated with higher inflammation in diabetic individuals 151 .…”
Section: Implications For Human Healthmentioning
confidence: 59%
“…This link between chronotype and misalignment was also suggested in a study of 163 prediabetic or type 2 diabetic individuals’ eating and sleeping patterns. This study found that, after adjusting for age, sex, BMI, and statin use, a late chronotype was associated with higher inflammation in diabetic individuals 151 .…”
Section: Implications For Human Healthmentioning
confidence: 59%
“…An evening circadian preference, also called extreme eveningness or evening chronotype, is hypothesized to be a proxy marker of circadian system dysfunction because of its association with circadian phase delay (23). A desynchronization between the components of the circadian system favored by a circadian phase delay in individuals with an evening chronotype may represent a potential mechanism for the associated adverse health outcomes (24)(25)(26)(27). Indeed, evening chronotype is associated with disorganized eating behavior, unhealthy food preferences, nighteating behavior, and binge-eating behavior (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular interest since subjects with EC tend to have more health problems, including psychological, neurological, and gastrointestinal morbidities, and higher mortality rates than MCs. [35][36][37] Epidemiological evidence has also linked EC to cardiovascular disease and cardiometabolic risk factors, including higher risk of overweight and obesity and type 2 diabetes. [37][38][39] In addition, subjects with EC are more likely to report poor healthy behaviors, such as higher rates of smoking, unhealthy diets, and later timing of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…In this framework, chronotype, which reflects interindividual differences in daily activity patterns and sleep‐wake cycles, 8 might be taken into account in lifestyle intervention in treatment of women with PCOS. This is of particular interest since subjects with EC tend to have more health problems, including psychological, neurological, and gastrointestinal morbidities, and higher mortality rates than MCs 35–37 . Epidemiological evidence has also linked EC to cardiovascular disease and cardiometabolic risk factors, including higher risk of overweight and obesity and type 2 diabetes 37–39 .…”
Section: Discussionmentioning
confidence: 99%